Health surveillance of workers - Ospina Salinas, Estela (2014)
In our legal system, fundamental rights to life and health of workers are important legallyprotected goods that cannot be disregarded. Therefore, the State and the   employers must put special emphasis on health and security surveillance of workers to prevent that employment relationships become an obstacle or a violation of such rights.In light of these precepts, the author makes an analysis of the protection given to these fundamental rights in our country. Basing on comparative legislation, she poses general concepts of  the State’s and the  employer´s responsibility of health and security surveillance of workers, allowing her to conclude that our system has still to confront many challenges in the path to achieve effective protection and enforcement of therights at stake.